Placental Polyp : A Rare Case Report - Yeasmin, Most Sabina; Nourin, Nishat Anjum; Begum, Tahera; Mabud, Farah Naz; Surovi, Farjana Ahmed (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Placental polyp is the retained fragment of placental tissue which presents as a polypoidal or pedunculated mass within the uterus. It is a rare entity and has an incidence of less than 0.25 % of all pregnancies. There are also very few reported cases of the clinical placental polyp. Here,we report a case of 22-year-old P1 woman presenting with vaginal bleeding and something coming down into vagina.Her last pregnancy had occurred one year ago.Laboratory investigation revealed slightly elevated serum b-hCG. Ultrasonography revealed thick endometrium, broad cervix (5.2cm) and a hyperechoic mass within the cervix. Extraction of the placental polyp followed by endometrial curettage were done and tissue sent for histopathology. Definite diagnosis was made by histopathological examination and which was a placental polyp. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 85-88